ANALYSIS OF WAYS TO INCREASE THE EFFICIENCY OF COMPRESSED AIR FOAM FOR EXTINGUISHING SOLID MATERIALS - Shakhov, S.; Vinogradov, S.; Grishenko, D. (Municipal economy of cities (Technical science), 2023)
Conduct an analysis of scientific periodicals regarding the use and improvement of the fire extinguishing efficiency of compression foam. The work was carried out on the basis of the analysis of scientific periodicals, experimental studies of scientists from the European Union, the USA, China and other countries, the results of which were presented in scientific publications, conferences and reports. Conclusions. An analysis of scientific publications devoted to the use of compression foam in firefighting and increasing its fire-fighting efficiency was carried out. It was found that the majority of research is aimed at studying the fire-extinguishing effectiveness of compression foam when extinguishing flammable liquids. In turn, there are studies devoted to increasing the fire-fighting efficiency of compression foam by varying the multiplicity and concentration of the aqueous solution of the foaming agent, changing the ratio of air/foaming agent solution, and the use of various types of foaming agents when extinguishing fires of solid combustible materials. To date, there are no studies aimed at increasing the efficiency of compression foam by adding modified additives to its composition. The result of the research is the identification of ways to increase the efficiency of compression foam today, due to which the direction of further research aimed at increasing the fire-extinguishing efficiency of the foam in other ways is revealed. The practical value lies in solving the actual problem of fire safety, namely increasing the efficiency of extinguishing fires of solid combustible substances, due to the use of compression foam. Thanks to the results of the analysis of further development, effective use of compression foam is acquired, the fire-extinguishing capacity of which can be increased by using modified additives in its composition. This provides an opportunity to expand the mechanisms of influence of the fire-extinguishing effect of compression foam on the burning process of solid combustible materials.